2019
DOI: 10.1177/1078155219855127
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparison of immune checkpoint inhibitors in non-small cell lung cancer following platinum-based chemotherapy

Abstract: Purpose Immunotherapy is a relatively new treatment modality for advanced non-small cell lung cancer following platinum-based chemotherapy. Nivolumab, pembrolizumab, and atezolizumab demonstrated superior outcomes and improved tolerability compared to standard treatment in randomized controlled trials; however, these studies vary significantly in inclusion criteria and study design. To our knowledge, the efficacy and safety of nivolumab and atezolizumab following platinum-based chemotherapy have not been direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
4
18
0
Order By: Relevance
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 76%
“…The vast majority of the real-world data about immunotherapy in lung cancer describes the activity, in terms of objective response rate (ORR), efficacy (in terms of overall survival, OS, and progression free survival, PFS) and the safety profile of the most common ICIs used in clinical practice (Table 1). Studies on pretreated NSCLC patients were all retrospective and showed outcomes comparable with those reported in the pivotal RCTs, with median PFS and median OS ranging from 1.8 to 4.9 months and from 7.9 to 14.6 months, respectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Only one study showed a remarkable outcome for patients treated with nivolumab, with a median PFS exceeding 8 months and a median OS of over 15 months; however, this may be due to the small population (n = 11) considered for analysis [23].…”
Section: Efficacy and Safety A Of Icis In The Real Worldmentioning
confidence: 76%
“…Atezolizumab and nivolumab, PD-L1 and PD-1 antibodies, respectively, are proven to be effective and safe in clinical trials [ 3 , 4 , 6 ] and after approval by authorities in real-world studies ( Table 1 ) [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, there is no head-to-head clinical trial that compares the results of each drug, and to our knowledge, there are only two real-world studies that have compared outcomes between the two ICIs [ 11 , 12 ]. However, they did not perform a head-to-head subgroup analysis between the two ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…This contrast in the real-world outcomes (PFS, OS and ORR) is due to several factors, such as the inclusion of a very heterogeneous population between studies that include patients who are generally excluded from clinical trials, including elderly patients, heavily pretreated, patients with an ECOG score greater than or equal to 2, CNS metastasis and/or with numerous comorbidities. For example, poor survival outcomes have been obtained in studies that include a high number of patients with negative prognostic factors such as ECOG ≥ 2 or metastases in the CNS [ 12 , 22 , 23 , 24 ]. In our cohort, 15.2% of patients had ECOG ≥ 2, and 16.5% had CNS metastases at baseline, similar to other real-world studies [ 9 , 16 , 17 ] and higher than those included in the pivotal studies, 1.5%, 0% and 0% for ECOG ≥ 2 and 6.6%, 11.6% and 10% for CNS metastases in Checkmate017, Checkmate057 and OAK, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have examined the real-world treatment patterns and clinical outcomes of these therapies. These studies have mostly included patients with previously treated advanced NSCLC, lacked comparisons between treatments, and/or limited the patient population to those with PD-L1 expression (Khozin et al 2018 ; Molife et al 2019 ; Nadler et al 2018 ; Schwartzberg et al 2019 ; Velcheti et al 2019 ; Weis et al 2019 ). Further research on IO use in patients with advanced NSCLC treated in the community oncology setting is needed, as there may be differences in real-world clinical outcomes compared with clinical trial outcomes due to underlying variation in patient populations and methodology (Khozin et al 2019a ).…”
Section: Introductionmentioning
confidence: 99%